1979
DOI: 10.2134/agronj1979.00021962007100040006x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Root Temperature on Shoot Growth of Two Kentucky Bluegrass Cultivars1

Abstract: Shoot growth inhibition and changes in carbohydrate levels occur in cool‐season grasses under midsummer conditions. Cultural practices, such at thatch removal or topdressing, could alter high temperature extremes of the crown and root. Thus, the objective of this study was to determine the role of root temperature on shoot growth rate and water soluble carbohydrate (WSC) levels in plant parts of ‘Merion’ and ‘Nugget’ Kentucky bluegrass (Poa pratensis L.). The turfgrasses were established from seed on coarse sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
1
14
1
Order By: Relevance
“…Although no studies specifically reporting these kinds of carbohydrate changes have been done for native grasses, including rough fescue, there are indications that Kentucky bluegrass (Poa pratensis L.), growing under controlled conditions and exposed to constant moderate temperature increases (i.e., 26 o C), may enhance carbohydrate use and subsequent shoot growth For personal use only. (Aldous and Kaufmann 1979). Notably, the temperature found to be stimulatory in the aforementioned study is considerably lower than the temperature documented here, although there are differences in both the nature of the heat treatments and their duration.…”
Section: Tiller Leaf Growth In Response To Temperature and Exposure Timecontrasting
confidence: 49%
“…Although no studies specifically reporting these kinds of carbohydrate changes have been done for native grasses, including rough fescue, there are indications that Kentucky bluegrass (Poa pratensis L.), growing under controlled conditions and exposed to constant moderate temperature increases (i.e., 26 o C), may enhance carbohydrate use and subsequent shoot growth For personal use only. (Aldous and Kaufmann 1979). Notably, the temperature found to be stimulatory in the aforementioned study is considerably lower than the temperature documented here, although there are differences in both the nature of the heat treatments and their duration.…”
Section: Tiller Leaf Growth In Response To Temperature and Exposure Timecontrasting
confidence: 49%
“…The indicated that the higher level of WSC in drought‐preconditioned plants contributed to higher osmotic adjustment with the prolonged heat stress. The accumulation of WSC in shoots with increasing high temperature has been observed in a tolerant cultivar of Kentucky bluegrass (Aldous and Kaufmann, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Deep rooting facilitates extraction of soil moisture from deeper soil profiles (Morgan and Condon, 1986; Tangpremsri et al, 1991). Higher WSC accumulation in roots could be beneficial for the maintenance of cell turgor and root penetration deeper into the soil profile (Sharp et al, 1990), and also associated with heat tolerance (Aldous and Kaufmann, 1979). Therefore, deeper root system and larger amount of WSC content could contribute to heat tolerance caused by drought‐preconditioning in Kentucky bluegrass.…”
Section: Discussionmentioning
confidence: 99%
“…(Beard, 1973). Root growth of Kentucky bluegrass ( Poa pratensis L.) was inhibited as soil temperature increased to 25°C (Aldous and Kaufmann, 1979). Root growth and initiation in creeping bentgrass stopped when soil temperature was above 25°C (Lucas, 1995; Beard and Sifers, 1997; Huang et al, 1998).…”
mentioning
confidence: 99%